The Antagonistic Potential of Kimchi-Associated LAB Against Histamine-Producing Pathogens in Seafood - Putu Satrio Jhanardana Dewantara; Ni Putu Bintang Diah Lastini; Made Okta Hapsari Putri Diarsa; Pande Gede Putra Satwika; Dwi Ariani Yuliastuti; I Dewa Agung Panji Dwipayana; Yan Ramona (Program Magister Ilmu Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2025)
Lactic acid bacteria (LAB) play a crucial role in food fermentation, for example in kimchi, a traditional Korean dish. These bacteria don’t only function in food preservation and probiotics, but also exhibit antimicrobial activity through the production of compounds like bacteriocins. This study introduces a novel approach in using LAB from kimchi for inhibiting the growth of Morganella morganii, a major histamine-producing pathogen in fish products. Histamine accumulation poses severe food safety risks, necessitating an innovative natural solutions. LAB isolates from both solid and liquid fractions of kimchi were screened on selective media and characterized biochemically for traits such as fermentation type and acid production. Antimicrobial efficacy, assessed via the Kirby-Bauer disk diffusion method, revealed inhibition zones averaging 6.98 ± 0.04 mm for liquid and 6.40 ± 1.34 mm for solid fractions. Despite their lower efficacy compared to chloramphenicol (30.80 ± 1.92 mm), the eco-friendly nature of LAB highlights their unique potential as a sustainable alternative for histamine control. This study is among the first to explore kimchi-derived LAB as antagonists against M. morganii, providing a novel perspective for developing green technologies in food safety and quality management.